Attitudes towards COVID-19 vaccine in Spain: correlational and configurational analyses - Jorge de Andrés-Sánchez; Mario Arias-Oliva; Jorge Pelegrin-Borondo (Intelektual Pustaka Media Utama, 2023)
This study explains attitude towards vaccination against COVID-19. It evaluates four cognitive, affective and normative (CAN) factors: fear of COVID-19 (FCOVID), fear of the vaccine (FVACC), efficacy (EFFICACY), and social influence (SOCINF) and three sociodemographic variables: gender, age, and income level. Ordered logistic regression showed a significant positive influence of FCOVID, EFFICACY and SOCINF and a negative impact of FVACC and income level (INCOME). Configurational analysis allowed observing that all evaluated factors are relevant for explaining the attitude towards vaccination and that the sign of the relationship in configurations between CAN factors and attitude is positive for FCOVID, EFFICACY and SOCINF and negative for FVACC. These variables symmetrically impact on willingness and unwillingness to use the vaccine. INCOME and regarding gender (GENDER) impact asymmetrically to induce acceptance and resistance to vaccination. The results in our paper have clear practical implications. Correlational analysis discovers the average strength of assessed factors on vaccine acceptation and so identifying the most relevant variables. On the other hand, configurational analysis identifies how factors combine to shape profiles of persons with willingness and unwillingness to get vaccinated. These last profiles are of special concern for health policy-makers since their resistance diminishes the effectivity of collective vaccination.